2011
DOI: 10.1002/hipo.20829
|View full text |Cite
|
Sign up to set email alerts
|

Chronic restraint stress in adolescence differentially influences hypothalamic‐pituitary‐adrenal axis function and adult hippocampal neurogenesis in male and female rats

Abstract: Previous studies have shown a relationship between adversity in adolescence and health outcomes in adulthood in a sex-specific manner. Adolescence is characterized by major changes in stress-responsive regions of the brain, including the hippocampus, the site of ongoing neurogenesis throughout the lifespan. Prepubertal male and female rats exhibit different acute reactions to chronic stress compared to adults, but less is known about whether these stress-induced changes persist into adulthood. Therefore, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
119
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 90 publications
14
119
0
Order By: Relevance
“…Stress exposure during certain vulnerability periods, including adolescence, is known to alter how the HPA axis responds to future stressors (Barha et al, 2011;Burke et al, 2010;Isgor et al, 2004;Weintraub et al, 2010). Therefore, chronic high levels of the hormone corticosterone, which is released by the adrenal glands after HPA axis activation, could produce permanent changes in response to stressors long after the CORT exposure has ended.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Stress exposure during certain vulnerability periods, including adolescence, is known to alter how the HPA axis responds to future stressors (Barha et al, 2011;Burke et al, 2010;Isgor et al, 2004;Weintraub et al, 2010). Therefore, chronic high levels of the hormone corticosterone, which is released by the adrenal glands after HPA axis activation, could produce permanent changes in response to stressors long after the CORT exposure has ended.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of differences in impulsivity observed here are unlikely to be explained by altered HPA axis function, but rather by long-lasting neuroplasticity in the circuits that regulate impulsive behavior and decision-making. Indeed, several studies involving adolescent stress exposure report that in adulthood the animals have no difference in baseline CORT levels, though they may have a reduction in peak CORT levels or faster negative feedback after an acute stressor (Weintraub et al, 2010;Burke et al, 2010;Barha et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, resting corticosterone levels and their responsiveness to additional stressors showed null or small effects (Giavanoli et al, 2013;Ilin and Richter-Levin, 2009;Jacobson-Pick et al, 2012;Maslova et al, 2002a;Sandi, 2007, 2011;Yee et al, 2011). Interestingly, there is some evidence for a stronger effect of stress during adolescence (prepubertal or posterior) on adult HPA reactivity to stress in females than in males (Barha et al, 2011;Bourke and Neigh, 2011;Jacobson-Pick et al, 2012;Pohl et al, 2007;Weathington et al, 2012), although these gender differences have not been found consistently McCormick et al, 2005McCormick et al, , 2008Toledo-Rodríguez and Sandi, 2007;Wright et al, 2008). The particular type of stressor may be one of the factors to account for those inconsistencies.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%